The Role of Corporate Social Responsibility in Promoting Quality Education in Ghana; The Case of Plan International Ghana. - Kodjo, David Bismark (UniMAC-GIJ, 2021)
Plan International Ghana is a non-profit making organization which was established for the past years been contributing to bridging the social amenities gab in rural communities across world with the aim of promoting inclusive and equitable quality education and ensuring peaceful and just societies. This dissertation tried to find out the role Non-Governmental Organizations play towards achieving the global 2030 Sustainable Development Goal Four (SDG4) in Ghana. The study is underpinned by the stakeholder theory and the Carroll’s (1991) Model of Corporate Social Responsibility were relevant theories for this study because of their ability in explaining the capabilities of non-state actors, such as Plan International Ghana to influence and contribute significantly to the educational development of several states including Ghana. The dissertation is a case study research and it adopts the qualitative research approach, using both secondary and primary data. The researcher used semi-structured interview guides and Focus Group Discussion (FGD) to collect the requisite primary data from the selected population in the Eastern Region of Ghana. The study found out that, Plan International contributed significantly to the attainment of the Sustainable Development Goal Four, which respectively measured the enrolment rate in primary schools and the literacy rate of youth in the said region. The study recommended that; the Government of Ghana should enact a Legislative Instrument to compel Non-Governmental Organizations (NGOs) to provide educational support to basic schools in the communities in which they operate. It is envisaged that this will enable children from typically difficult-to-reach groups such as those from disadvantaged economic and ethnic groups; those with disabilities; and those of nomadic origin within the rural areas of the Eastern Region and other rural areas of the country to have access to inclusive and equitable quality education.
Thesis
Keywords: Corporate Social Responsibility, Promoting Quality Education, Ghana, Plan International, Ghana